Corrosion Behavior of AISI 1045 Steel in Seawater in the Presence of Flavobacterium sp. - Wu, Jinyi; Zhang, Weixiong; Chai, Ke; Yu, Aimin (Frontiers in Microbiology, 2020)
A systematic comparison study was carried out to investigate the effect of Flavobacterium sp. on AISI 1045 steel corrosion by weight loss, fluorescence microscopy (FM), surface analysis, cell count, pH measure, electrochemical impedance spectroscopy (EIS) and polarization curves. The impedances were considerably increased by Flavobacterium sp. between 1 and 7 day exposure and after 30 day exposure but considerably decreased by Flavobacterium sp. after 15 and 21 day exposure, which were supported by the Icorr results and the weight loss data. Furthermore, the biofilm was formed on the coupons. The pH values were considerably decreased by Flavobacterium sp. after 15 and 21 day exposure. The results proved that Flavobacterium sp. decreased the corrosion rates between 1 and 7 day exposure and after 30 day exposure and increased the corrosion rates between 15 and 21 day exposure, which could be ascribed to the protective biofilm and the secreted corrosive acid, respectively. In addition, Flavobacterium sp. considerably increased the pit numbers, the maximum pit depths and the corresponding widths and considerably decreased the Epit values. Importantly, the coverage and the heterogeneity of the biofilm were positively correlated with the increases in the maximum pit depths and the corresponding widths and the decreases in the Epit values by Flavobacterium sp.. The results demonstrated that Flavobacterium sp. increased the pitting corrosion, which could involve the heterogeneous biofilm cover.